Moving beyond the first timber harvesting in managed tropical forests in eastern Amazon: long-term responses to the recovery of structure, biomass and natural regeneration of tree species - Pinto, Rodrigo Costa (2025)
Long-term studies on the effects of logging on forest recovery, biomass, and tree species regeneration remain limited. Harvesting intensity directly influences structural recovery and the replenishment of commercial species for future harvest cycles. In this thesis, we analyze the long-term recovery of forest structure, biomass, and natural regeneration under two selective logging methods: reduced-impact logging (RIL) and conventional logging (CL) in a managed area in the eastern Amazon. The thesis is divided into four chapters: the first presents the general introduction, while the others explore technical and scientific aspects. In Chapter 2, we examine the recovery of aboveground biomass 24 years after harvesting under RIL and CL. Chapter 3 assesses forest structural recovery after 30 years, focusing on parameters such as total volume and biomass. Chapter 4 investigates the regeneration of logging gaps, which tend to recover more slowly due to the high initial impact. In the final chapters, we combine field inventory data with LiDAR (Light Detection and Ranging) metrics, providing a comprehensive analysis of forest recovery. The results show that both methods contribute to forest recovery after the first harvest cycle, but RIL stands out for promoting higher biomass, total volume, and better forest structure. While tree density and species diversity do not differ significantly between methods, variations in light availability, floristic composition, and ecological groups suggest that logging impacts regeneration dynamics. We hope that the findings of this thesis will enhance the understanding of long-term forest recovery in managed areas, demonstrating that both methods support post-harvest regeneration, with RIL offering superior structural and functional benefits. Additionally, well-managed forests tend to be more resilient to extreme droughts, which are becoming increasingly frequent in the tropics, making RIL an effective strategy for mitigating climate change, reducing greenhouse gas emissions, and strengthening financial mechanisms such as REDD+.